Fannie in the kitchen - Hopkinson, Deborah (Atheneum Books for Young Readers, 2001)
Fannie Farmer is a mother's helper in the Shaw house, where the daughter gives her the idea of writing down precise instructions for measuring and cooking, which eventually became one of the first modern cookbooks.